2023
DOI: 10.3390/app13042743
|View full text |Cite
|
Sign up to set email alerts
|

A Comprehensive Review of Conventional, Machine Leaning, and Deep Learning Models for Groundwater Level (GWL) Forecasting

Abstract: Groundwater level (GWL) refers to the depth of the water table or the level of water below the Earth’s surface in underground formations. It is an important factor in managing and sustaining the groundwater resources that are used for drinking water, irrigation, and other purposes. Groundwater level prediction is a critical aspect of water resource management and requires accurate and efficient modelling techniques. This study reviews the most commonly used conventional numerical, machine learning, and deep le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(20 citation statements)
references
References 97 publications
0
7
0
Order By: Relevance
“…This paper provides a synthesis of the state of the art on wireless underground sensor networks (WUSNs) and Internet of underground things (IoUT) applied to smart farming. Guided by [15,16], we first formulated two research questions, namely, which approaches have been developed in the literature to build WUSNs and how the data can be collected from either ground relays, mobile robots or UAVs.…”
Section: Methodsmentioning
confidence: 99%
“…This paper provides a synthesis of the state of the art on wireless underground sensor networks (WUSNs) and Internet of underground things (IoUT) applied to smart farming. Guided by [15,16], we first formulated two research questions, namely, which approaches have been developed in the literature to build WUSNs and how the data can be collected from either ground relays, mobile robots or UAVs.…”
Section: Methodsmentioning
confidence: 99%
“…Nowadays, AI methods have been successfully employed for GWL modelling and prediction in aquifers of different geological and climatic regions (Daneshvar Vousoughi, 2022; Khan et al, 2023; Naghipour et al, 2023; Rajaee et al, 2019). In this field, long short‐term memory (LSTM) has found extensive application in this domain (Shahabi‐Haghighi & Hamidifar, 2023).…”
Section: Introductionmentioning
confidence: 99%
“…Across the literature, various popular forecasting approaches have been tested on specific applications of groundwater level forecasting, including Auto-Regressive Integrated Moving Average (ARIMA), Artificial Neural Networks (ANN), Long Short-Term Memory (LSTM) as well as hybrid approaches such as ARIMA-LSTM [38][39][40][41]. Comparative studies have consistently shown that machine learning-based methods outperform traditional numerical approaches [42] with superior prediction performance and capturing complex and non-linear relationships between input and output variables [43]. In a bibliometric study of machine learning and mathematical modeling techniques of forecasting using piezometric data [44], authors find that machine learning techniques such as Random Forest (RF), Support Vector Machine (SVM), and deep learn-ing techniques like ANN achieve higher accuracies if compared to mathematical model techniques.…”
Section: Introductionmentioning
confidence: 99%